The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1111/j.1528-1157.1984.tb03454.x
|View full text |Cite
|
Sign up to set email alerts
|

Radioiodide Uptake in Brain, CSF, Thyroid, and Salivary Glands of Audiogenic Seizure Mice

Abstract: DBA/2J (DBA) mice are susceptible to audiogenic seizures (ASs) in an age-dependent manner. Anion transport as measured by radioiodide uptake was determined in thyroid gland, salivary gland, skeletal muscle, cerebral cortex, cerebellum, brainstem, and CSF from these mice at various ages. Anion transport was also determined in C57BL/6J(C57) mice, an AS-resistant strain. In thyroid, DBA mice had an enhanced ability to concentrate iodide at 21 days of age when they have maximal AS susceptibility, as compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…Since the role of CA in salivary gland tissue is uncertain, a decrease in activity of this enzyme here is of uncertain consequence. However, this finding does give additional support for an inverse relation between CA activity and 1251 transport, since 1251 transport is increased in salivary gland tissue from DBA mice at 21 days of age (Engstrom et al, 1984).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Since the role of CA in salivary gland tissue is uncertain, a decrease in activity of this enzyme here is of uncertain consequence. However, this finding does give additional support for an inverse relation between CA activity and 1251 transport, since 1251 transport is increased in salivary gland tissue from DBA mice at 21 days of age (Engstrom et al, 1984).…”
Section: Discussionmentioning
confidence: 82%
“…This relation is also present in DBA mice at 21 days. Thus, 1251 uptake studies in 21-day-old DBA mice demonstrated a decrease in iodide transport in cerebral cortex (Engstrom et al, 1984), and the present investigation demonstrated an increase in CA activity in cerebral cortex homogenates from DBA mice at this age. This finding may be explained if bicarbonate and iodide compete for the same transport system.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additional studies have shown that there is a decrease in anion transport in cerebral cortical cells of DBA mice at the age of maximal susceptibility to AGSs (Engstrom et al, 1984). Also, it has been shown that there is a decrease in density and an increase in atfinity of GABA binding sites in brain from DBA mice when they are susceptible to AGSs (see review by Seyfried, 1982).…”
Section: Discussion Mest Glycine and Excitatory Amino Acidsmentioning
confidence: 96%
“…Thus, because anion transport systems are compromised in brain from DBA mice (Engstrom et al, 1984a), an increase in CA activity may be aimed at overcoming this defect. Also, increased CA activity may be a response to handle a greater metabolic load of C 0 2 resulting from neuronal hyperactivity in these seizuresusceptible mice.…”
Section: Chronic Actz Administration: Effects On Actz Eds0 Values Andmentioning
confidence: 98%